Heteroatom-substituted rhodamine dyes: Structure and spectroscopic properties - Deng, Fei; Xu, Zhaochao (Chinese chemical letters, 2019)
This review summarized the structures and photophysical properties of heteroatom-substituted rhodamines. [Display omitted] Rhodamine is one class of most popular dyes used in fluorescence imaging due to the outstanding photoproperties including high brightness and photostability. In recent years, replacement the xanthene oxygen with other elements, especially silicon, has attracted great attentions in the development of new rhodamine derivatives. This review summarized the structures and photophysical properties of heteroatom-substituted rhodamines. We hope this review can help to understand the structure-property relationships of rhodamine dyes and then elucidate the way to create derivatives with improved photoproperties.